Adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane

By preparing and applying specific composition adsorbents, the problem of the removal of hexamethylcyclotrisiloxane in the production of octamethylcyclotetrasiloxane requires heating and reflux, achieving efficient removal at room temperature, reducing energy consumption and Improves product purity.

CN116459786BActive Publication Date: 2024-12-24SUZHOU JINHONG GAS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310470124.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2024-12-24
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

In the prior art, the removal of the by-product hexamethylcyclotrisiloxane during the production process of octamethylcyclotetrasiloxane requires heating and reflux, resulting in higher energy consumption.

Method used

Adsorbents including tetrapropyl ammonium bromide, sodium hydroxide, aluminum sulfate, vapor phase silica and copper or nickel are prepared by hydrothermal reaction and calcination, and the pore size of molecular sieve is controlled to achieve hexamethyl at room temperature. Directed adsorption and removal of cyclotrisiloxane.

Benefits of technology

The energy consumption of hexamethylcyclotrisiloxane removal in the production process of octamethylcyclotetrasiloxane is effectively reduced, with a removal rate of 99.68%, and the purification of octamethylcyclotetrasiloxane is achieved at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116459786B_ABST
    Figure CN116459786B_ABST
Patent Text Reader

Abstract

The present application discloses an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, comprising the following raw materials by weight: 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 0.89-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 parts of copper sulfate or 0.15 parts of nickel nitrate hexahydrate. The present application can accurately control the pore size of the molecular sieve by selecting a silicon source, a template agent, an alkali source, an aluminum source, a copper source and a nickel source and controlling the proportion of the raw materials, and produce an adsorbent that can directional adsorb and separate hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, purify octamethylcyclotetrasiloxane at room temperature, and effectively reduce the energy consumption of removing the byproduct hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane; the adsorbent has excellent selective adsorption performance, and the removal rate of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane reaches 99.68%, and the concentration of hexamethylcyclotrisiloxane after adsorption can be reduced to 1.60ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of molecular sieve adsorbents, and in particular relates to an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane. Background Art

[0002] Octamethylcyclotetrasiloxane [(CH3)2SiO]4 can be used as a universal starting material for the production of viscous dimethylpolysiloxane oils, dimethylpolysiloxane gums, etc. suitable for conversion into silicone elastomers.

[0003] As the requirements for organosilicon performance become higher and higher, the demand for high-purity octamethylcyclotetrasiloxane is increasing. At present, the by-product hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane is removed by distillation, which requires heating and reflux. Since the boiling point of octamethylcyclotetrasiloxane is as high as 175 degrees, it will generate high energy consumption. Summary of the invention

[0004] The purpose of the present application is to provide an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, so as to solve the technical problem in the prior art that the by-product hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane is removed by distillation and light removal, which requires heating and reflux, resulting in high energy consumption.

[0005] To achieve the above purpose, a technical solution adopted in this application is:

[0006] Provided is an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, comprising the following raw materials in parts by weight:

[0007] 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 0.89-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 part of copper sulfate or 0.15 part of nickel nitrate hexahydrate.

[0008] In one or more embodiments, the following raw materials are included in weight:

[0009] 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 1-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 part of copper sulfate.

[0010] In one or more embodiments, the following raw materials are included in weight:

[0011] 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 1-1.20 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.15 parts of nickel nitrate hexahydrate.

[0012] To achieve the above purpose, another technical solution adopted by this application is:

[0013] A method for preparing the adsorbent according to any of the above embodiments is provided, comprising:

[0014] Weigh the raw materials in proportion, add them into deionized water and mix them evenly to obtain a mixed solution;

[0015] grinding the mixed liquid to obtain a grinding liquid;

[0016] The grinding liquid is placed in a reactor for hydrothermal reaction, cooled to room temperature after the reaction is completed, and washed and filtered in sequence to obtain a solid powder;

[0017] The solid powder is calcined to obtain the adsorbent.

[0018] In one or more embodiments, the step of grinding the mixed solution is specifically: inputting the mixed solution into a ball mill and ball milling for 20 to 28 hours.

[0019] In one or more embodiments, the hydrothermal reaction is specifically: reacting at 170-190° C. for 20-28 hours.

[0020] In one or more embodiments, the step of calcining the solid powder is specifically: calcining the solid powder at 480-520° C. for 5-7 hours.

[0021] To achieve the above purpose, another technical solution adopted by this application is:

[0022] Provided is an application of an adsorbent prepared by the preparation method described in any one of the above embodiments in removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane.

[0023] In one or more embodiments, the adsorbent is added to octamethylcyclotetrasiloxane and allowed to stand for adsorption for 20 to 28 hours.

[0024] In one or more embodiments, the mass ratio of the adsorbent to the octamethylcyclotetrasiloxane is (1.8-2.2):10.

[0025] In one or more embodiments, the removal rate of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane after adsorption by the adsorbent is greater than 98.5%.

[0026] Different from the prior art, the beneficial effects of this application are:

[0027] The preparation method of the present application can accurately control the pore size of the molecular sieve by selecting a silicon source, a template agent, an alkali source, an aluminum source, a copper source, and a nickel source and controlling the ratio of raw materials, and produce an adsorbent capable of directional adsorption and separation of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane, thereby achieving purification of octamethylcyclotetrasiloxane at room temperature, and effectively reducing the energy consumption of removing the byproduct hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane;

[0028] The adsorbent of the present application has excellent selective adsorption performance, and the removal rate of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane reaches 99.68%. After adsorption, the concentration of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane can be reduced to 1.60 ppm. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane according to the present application. DETAILED DESCRIPTION

[0030] The present application will be described in detail below in conjunction with the various embodiments shown in the accompanying drawings. However, these embodiments do not limit the present application, and any structural, methodological, or functional changes made by a person of ordinary skill in the art based on these embodiments are all within the scope of protection of the present application.

[0031] As shown in the background technology, currently, the by-product hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane is removed by distillation and light removal, which requires heating and reflux. Since the boiling point of octamethylcyclotetrasiloxane is as high as 175 degrees, it will generate high energy consumption.

[0032] In order to solve the above problems, the applicant has developed an adsorbent that can accurately separate hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane. The adsorbent uses the molecular sieve effect to directional adsorb and separate hexamethylcyclotrisiloxane, and can purify octamethylcyclotetrasiloxane at room temperature.

[0033] Specifically, the adsorbent for accurately separating hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane in the present application includes the following raw materials in parts by weight: 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 0.89-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 part of copper sulfate or 0.15 part of nickel nitrate hexahydrate.

[0034] The present application also provides a method for preparing an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, see Figure 1 , Figure 1 It is a schematic flow chart of an embodiment of a method for preparing an adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane according to the present application.

[0035] The preparation method comprises:

[0036] S100, weigh raw materials according to proportion, add them into deionized water and mix them evenly to obtain a mixed solution.

[0037] S200, grinding the mixed liquid to obtain a grinding liquid.

[0038] First, the raw materials may be mixed in deionized water and then ground to fully mix the raw materials and break them into fine particles.

[0039] In one embodiment, the grinding method may be to input the mixed solution into a ball mill and grind it for 20 to 28 hours; in other embodiments, other methods may be used for grinding, and the effects of the present embodiment may be achieved.

[0040] S300, placing the grinding liquid into a reactor for hydrothermal reaction, cooling to room temperature after the reaction is completed, and washing and filtering in sequence to obtain a solid powder.

[0041] After grinding is completed, the grinding liquid is subjected to a hydrothermal reaction. During the hydrothermal reaction, each raw material is crystallized; then, the solid powder is obtained by washing and filtering.

[0042] In one embodiment, the hydrothermal reaction may be specifically: reacting at 170-190° C. for 20-28 hours.

[0043] S400, calcining the solid powder to obtain an adsorbent.

[0044] In one embodiment, the calcination may specifically include: calcining the solid powder at 480-520° C. for 5-7 hours.

[0045] The present application can accurately control the pore size of the molecular sieve by selecting a silicon source, a template agent, an alkali source, an aluminum source, a copper source, and a nickel source and controlling the ratio of raw materials, and produce an adsorbent that can directional adsorb and separate hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, thereby achieving purification of octamethylcyclotetrasiloxane at room temperature, and effectively reducing the energy consumption of removing the by-product hexamethylcyclotrisiloxane in the production process of octamethylcyclotetrasiloxane.

[0046] The effects of the technical solution of the present application are further elaborated in detail below in conjunction with specific embodiments.

[0047] Embodiment 1:

[0048] An adsorbent is prepared by the following method:

[0049] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 4.73 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0050] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0051] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0052] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0053] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0054] Embodiment 2:

[0055] An adsorbent is prepared by the following method:

[0056] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 3.53 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0057] The mixed solution was input into a ball mill and ball-milled for 20 h;

[0058] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 170 degrees for 28 hours;

[0059] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0060] The solid powder was calcined at 520°C for 5 h to obtain the adsorbent.

[0061] Embodiment 3:

[0062] An adsorbent is prepared by the following method:

[0063] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.85 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0064] The mixed solution was input into a ball mill and ball-milled for 28 hours;

[0065] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 190 degrees for 20 hours;

[0066] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0067] The solid powder was calcined at 480°C for 7 h to obtain the adsorbent.

[0068] Embodiment 4:

[0069] An adsorbent is prepared by the following method:

[0070] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.33 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0071] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0072] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0073] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0074] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0075] Embodiment 5:

[0076] An adsorbent is prepared by the following method:

[0077] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.03 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0078] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0079] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0080] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0081] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0082] Embodiment 6:

[0083] An adsorbent is prepared by the following method:

[0084] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 1.73 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.1 g of copper sulfate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0085] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0086] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0087] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0088] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0089] Embodiment 7:

[0090] An adsorbent is prepared by the following method:

[0091] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 4.73 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add them into 12 g of deionized water and mix well to obtain a mixed solution;

[0092] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0093] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0094] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0095] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0096] Embodiment 8:

[0097] An adsorbent is prepared by the following method:

[0098] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 3.53 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add them into 12 g of deionized water and mix well to obtain a mixed solution;

[0099] The mixed solution was input into a ball mill and ball-milled for 20 h;

[0100] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 170 degrees for 28 hours;

[0101] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0102] The solid powder was calcined at 520°C for 5 h to obtain the adsorbent.

[0103] Embodiment 9:

[0104] An adsorbent is prepared by the following method:

[0105] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.85 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add them into 12 g of deionized water and mix well to obtain a mixed solution;

[0106] The mixed solution was input into a ball mill and ball-milled for 28 hours;

[0107] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 190 degrees for 20 hours;

[0108] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0109] The solid powder was calcined at 480°C for 7 h to obtain the adsorbent.

[0110] Embodiment 10:

[0111] An adsorbent is prepared by the following method:

[0112] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.33 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add them into 12 g of deionized water and mix well to obtain a mixed solution;

[0113] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0114] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0115] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0116] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0117] Embodiment 11:

[0118] An adsorbent is prepared by the following method:

[0119] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 2.03 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add them into 12 g of deionized water and mix well to obtain a mixed solution;

[0120] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0121] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0122] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0123] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0124] Embodiment 12:

[0125] An adsorbent is prepared by the following method:

[0126] Weigh 2.5 g of tetrapropylammonium bromide, 5 g of sodium hydroxide, 1.73 g of aluminum sulfate 18hydrate, 12.6 g of fumed silica, and 0.15 g of nickel nitrate hexahydrate, add to 12 g of deionized water and mix well to obtain a mixed solution;

[0127] The mixed solution was input into a ball mill and ball-milled for 24 hours;

[0128] The ball-milled material was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180 degrees for 24 hours;

[0129] The reacted material is cooled to room temperature, and then washed and filtered to obtain a solid powder;

[0130] The solid powder was calcined at 500°C for 6 h to obtain the adsorbent.

[0131] The raw material ratios of Examples 1 to 12 are specifically shown in the following table:

[0132]

[0133] Effect example:

[0134] The adsorbents prepared in Examples 1 to 12 were used for adsorption performance experiments. The specific experimental method is as follows:

[0135] Octamethylcyclotetrasiloxane containing 500 ppm hexamethylcyclotrisiloxane was prepared;

[0136] Take 20g of the adsorbent and add it to 100g of octamethylcyclotetrasiloxane containing 500ppm of hexamethylcyclotrisiloxane, and let it stand for adsorption at room temperature for 24h;

[0137] After the adsorption was completed, the mixture was filtered and the concentration of hexamethylcyclotrisiloxane in the adsorbed octamethylcyclotetrasiloxane was detected by gas chromatography to obtain the data in the following table.

[0138]

[0139] As shown in the above data, after adsorption by the adsorbents of Examples 1 to 6 including the copper source component, the removal rates of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane were all greater than 98.5%, and the concentration of hexamethylcyclotrisiloxane with a concentration of 500 ppm before adsorption was less than 7.3 ppm after adsorption. Among them, the concentration of hexamethylcyclotrisiloxane after adsorption by the adsorbent of Example 3 was as low as 1.6 ppm, and the removal rate was as high as 99.68%.

[0140] After adsorption by the adsorbents of Examples 7 to 12 including the nickel source component, the removal rates of hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane were all greater than 97.74%, and the concentration of hexamethylcyclotrisiloxane with a concentration of 500 ppm before adsorption was less than 11.30 ppm after adsorption. Among them, the concentration of hexamethylcyclotrisiloxane after adsorption by the adsorbent of Example 11 was as low as 2.3 ppm, and the removal rate was as high as 99.54%.

[0141] It can be seen from the above data that the adsorbent of the present application can efficiently and directionally adsorb and remove hexamethylcyclotrisiloxane in octamethylcyclotetrasiloxane at room temperature, and the removal rate can be as high as over 99.5%.

[0142] The removal rates of hexamethylcyclotrisiloxane by the adsorbents of Examples 1 to 5 are all greater than 99%. At this time, the mass range of aluminum sulfate 18hydrate is 2.03 to 4.73 g, that is, the mass range of aluminum sulfate is 1 to 2.43 g. The aluminum source content in Example 6 is too little, resulting in a decrease in the removal rate.

[0143] In the adsorbents of Examples 1 to 6, as the aluminum source content decreases, the removal rate shows a trend of first increasing and then decreasing. The adsorbent of Example 3 has a removal rate of 99.68% for hexamethylcyclotrisiloxane. Therefore, Example 3 is taken as a preferred example using a copper source component.

[0144] The removal rates of hexamethylcyclotrisiloxane by the adsorbents of Examples 10 and 11 are both greater than 99%. At this time, the mass range of aluminum sulfate 18hydrate is 2.03 to 2.33 g, that is, the mass range of aluminum sulfate is 1 to 1.20 g. In Example 7, the aluminum source content is too high, resulting in a low removal rate. In Example 12, the removal rate is affected due to the low aluminum source content.

[0145] As the aluminum source content in the adsorbents of Examples 7 to 12 decreases, the removal rate also shows a trend of first increasing and then decreasing. Among them, the removal rate of hexamethylcyclotrisiloxane by the adsorbent of Example 11 reaches 99.54%. Therefore, Example 11 is used as a preferred embodiment of using a nickel source component.

[0146] The above description of the present disclosure is provided to enable any person of ordinary skill in the art to implement or use the present disclosure. Various modifications to the present disclosure will be apparent to those of ordinary skill in the art, and the general principles corresponding to the present disclosure may be applied to other variations without departing from the scope of protection of the present disclosure. Therefore, the present disclosure is not limited to the examples and designs described herein, but is consistent with the widest range of principles and novel features disclosed herein.

Claims

1. An adsorbent for removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane, characterized in that: It includes the following raw materials in parts by weight: 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 0.89-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 part of copper sulfate or 0.15 part of nickel nitrate hexahydrate; The preparation method of the adsorbent comprises: Weigh the raw materials in proportion, add them into deionized water and mix them evenly to obtain a mixed solution; grinding the mixed liquid to obtain a grinding liquid; The grinding liquid is placed in a reactor for hydrothermal reaction, cooled to room temperature after the reaction is completed, and washed and filtered in sequence to obtain a solid powder; The solid powder is calcined to obtain the adsorbent.

2. The adsorbent according to claim 1, characterized in that It includes the following raw materials in parts by weight: 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 1-2.43 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.1 part of copper sulfate.

3. The adsorbent according to claim 1, characterized in that It includes the following raw materials in parts by weight: 2.5 parts of tetrapropylammonium bromide; 5 parts of sodium hydroxide; 1-1.20 parts of aluminum sulfate; 12.6 parts of fumed silica; 0.15 parts of nickel nitrate hexahydrate.

4. The adsorbent according to claim 1, characterized in that The step of grinding the mixed solution is specifically: inputting the mixed solution into a ball mill and grinding it for 20 to 28 hours.

5. The adsorbent according to claim 1, characterized in that The hydrothermal reaction is specifically: reacting at 170-190° C. for 20-28 hours.

6. The adsorbent according to claim 1, characterized in that The step of calcining the solid powder is specifically: calcining the solid powder at 480-520° C. for 5-7 hours.

7. Use of the adsorbent according to any one of claims 1 to 6 in removing hexamethylcyclotrisiloxane from octamethylcyclotetrasiloxane.

8. The use according to claim 7, characterized in that: The adsorbent is added into octamethylcyclotetrasiloxane and allowed to stand for adsorption for 20 to 28 hours.

9. The use according to claim 7, characterized in that: The mass ratio of the adsorbent to the octamethylcyclotetrasiloxane is (1.8-2.2):10.